Community gardens: contribution to food safety and social inclusion - Santos, Lucas Sales dos; Régis, Milena de Moura; Nascimento, Ana Paula Branco do (National Journal of City Management, 2021)
Sustainability in large-scale food production is one of humanity's greatest contemporary challenges. Today’s society is totally dependent on agricultural fields. In face of the increasing environmental and food crisis in the world, it is necessary to improve ways of promote sustainable agriculture. Conventional agriculture has proved to be predatory to the environment and maleficent to human health due to the intensive use of agrochemicals, and also inefficient to supply with quality and safety the whole urban population. Therefore, urban agroecology has become a tendency. The study presented here investigated a community garden of the West Zone of São Paulo City, organically grown in the Previdência Municipal Park, which is an intensely urbanized area. Observations were carried out in loco, plus interviews with the responsible for the community garden, and compilation of relevant literature, focusing on the importance of horticulture, practical difficulties in the community involved in the project, benefits to society, and the role in urban sustainability. Horticulturists’ social aspects, involvement of the regulars, and adopted cultivation techniques were also investigated. The challenges of urban agriculture projects reported in the literature were identified, so as to define the best cultivation strategies to be adopted in the community garden. The main results pointed to benefits to food and nutrition safety, interpersonal involvement, and environmental education; the main challenges consist of social leaderships, technical-scientific knowledge regarding productivity of organic cultivars, and planning aiming the continuity of the projects. Relevant benefits can be obtained from the implementation of urban garden projects, contemplating some of the Objectives of Sustainable Development that are related not only to sustainable agriculture, but also to the sustainability of cities and communities. KEYWORDS: Urban Agriculture. Food Safety. Urban Parks. Sustainability.